1980
DOI: 10.5254/1.3535079
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Isolation: Use and Characterization

Abstract: This article is concerned with vibration isolation, with antivibration mountings (resilient isolators), and with the static and dynamic properties of rubberlike materials that are suited for use in antivibration mountings. The design of practical antivibration mounts incorporating rubber or coiled-steel springs is described in Refs. 1–27; pneumatic isolators (air mounts, etc.) are described in Refs. 5, 28–35. Throughout the literature, as here, attention is focussed predominantly on the translational (vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The study of the connection type has been omitted but this is an important issue that should be analysed by means of three-dimensional models [7]. The literature review of Section 2 reveals that resilient devices tested in the laboratory are usually characterised by means of a four-pole parameter analysis [23] (also called two-port parameter analysis in [28]), but double wall models usually consider the stud to be a translational or rotational elastic spring.…”
Section: The Characterisation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the connection type has been omitted but this is an important issue that should be analysed by means of three-dimensional models [7]. The literature review of Section 2 reveals that resilient devices tested in the laboratory are usually characterised by means of a four-pole parameter analysis [23] (also called two-port parameter analysis in [28]), but double wall models usually consider the stud to be a translational or rotational elastic spring.…”
Section: The Characterisation Methodsmentioning
confidence: 99%
“…Most of the techniques were originally developed in order to determine the properties of rubber-like materials that are used as vibration isolators. An extensive literature review can be found in [23]. The consequence of this background is a set of ISO regulations establishing the basis of this kind of measurements [24].…”
Section: Experimental Measurementsmentioning
confidence: 99%
“…Supplemental passive dampers (Fu and Kazai, 1998;Sorace and Terenzi, 2008) and base-isolation systems (Snowdon, 1979) are used in many aspects of structural engineering for mitigation of excessive dynamic response (Symans et al, 2008). However, improved damping performance compared to the passive case may be obtained by combining pure energy dissipating installations with active elements to form so-called active/passive or hybrid damper systems (Thenozhi and Yu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The engine is the largest concentrated mass in a vehicle and causes vibration if it is not properly isolated and constrained. The trend for many years to isolate vibrations was to simply connect the engine and frame by means of an engine mount made of elastomeric materials such as rubber [1][2][3]. Modeling the rubber isolator by a linear system and considering a base excited single-degree-offreedom system, we know in the frequency response curves of the acceleration transmitted to the isolated mass there exists a crossing point at a frequency ratio value of ω/ω n = 2 1/2 in which all the curves representing systems with differing damping ratios converge [4].…”
Section: Introduction and Statement Of Problemmentioning
confidence: 99%